„Edukator rodzinny” w starzejącym się społeczeństwie. Mieć potrzeby i być potrzebnym ucząc się przez całe życie - Konieczna-Woźniak, Renata (Studia Edukacyjne, 2024)
The article aims to present the possibilities of using older people’s knowledge, skills, competencies, and wisdom as educators of the younger generation, especially in a family environment. The text also raises the issue of the possible meeting of older people’s psychosocial needs through the education of young people. The satisfaction of being a “family educator” may increase the level of motivation to continue meeting needs. The effects of the young generation learning from the older generation, discussing them, and using them by students during teaching classes are becoming an interesting and important topic. They point out the value of this education and its building intergenerational relationships in times of increasing generational separation.